Judgment day intelligent design on trial - McMaster, Joseph; Johnstone, Gary, 1959-; Tovell, Vanessa; Vulcan Productions; Big Table Film Company ([Boston, Mass.] : WGBH Boston Video, 2008)
"Judgment day: intelligent design on trial" captures the turmoil that tore apart the community of Dover, Pennsylvania, in a landmark battle over the teaching of evolution in public schools. In 2004, the Dover school board ordered science teachers to read a statement to high school biology students about an alternative to Darwin's theory of evolution called intelligent design--the idea that life is too complex to have evolved naturally and so must have been designed by an intelligent agent. The teachers refused to comply, and both parents and teachers filed a lawsuit in federal court accusing the school board of violating the constitutional separation of church and state. ... Featuring trial reenactments based on court transcripts and interviews with key participants and expert scientists, this program presents the case of Kitzmiller v. Dover School District."--Container.
Darwin in the classroom -- Evolution or intervention? -- Taking stands -- Darwin and the human genome -- Dover divided -- The bacterial flagellum -- The smoking gun -- The wedge -- The verdict and its aftermath.
DVD, NTSC; region 1.
Closed-captioned; with optional audio description for the visually impaired.
Lewis Hancock, Nigel Whitney, Richard Laing, James Jordan, Debora Weston, Glenn Wragg, Jay Benedict, Jeff Harding.
Editor, Jonathan Sahula ; narrator, Jay O. Sanders ; music, Rob Morsberger ; directors of photography, Christopher Titus King ... [et al.].
Originally broadcast on Nov. 13, 2007 as an episode of the PBS television program, Nova.
Copyright date on credit frame: 2007; copyright date on container: 2008.
Keywords: Evolution (Biology) -- Study and teaching -- Pennsylvania -- Dover; Intelligent design (Teleology) -- Study and teaching -- Pennsylvania -- Dover; Evolution (Biology) -- Study and teaching -- Law and legislation -- Pennsylvania -- Dover; Creationism -- Study and teaching -- Law and legislation -- Pennsylvania -- Dover; Intelligent design (Teleology) -- Study and teaching (Secondary); Documentary television programs; Educational television programs; Science television programs; Television programs; Television programs -- United States; Video recordings for hard of hearing people; Video recordings for people with visual disabilities; Documentary -- Television specials